The musealization of “platformized” phonography: Brazilian popular song as an aural collection in the 21st century (PerCursos, 2024)
Starting from the premise that the social and technological changes that involve the production and circulation of popular music today, in the tension between materiality and immateriality, with the decline of certain media, the rise of others, such as streaming platforms, challenge museums of Image and Sound (MIS) typology to develop new museological policies in view of the risk of gaps in their collections, hindering the production of memory and history regarding Brazilian popular song in the 21st century. To this end, I first propose to historically examine the constitution of what I am calling “aural object”, that is, the sound – and consequently, popular music – captured as a record by the advent of phonography, and its subsequent insertion into the institutionalized scenarios of heritage safeguarding, highlighting the Brazilian context. In the second section of the text, I will synthetically address the transformations undergone by phonography in digital media. I will bring, on an experimental and complementary basis, empirical material collected in ongoing research on MIS-SP, highlighting among its regular activities the Estéreo MIS project, dedicated to promoting live musical shows and audiovisual recordings through interviews concerning artists associated with the so-called “independent music” in Brazil. Privileging the analysis of some of these testimonies, I seek to demonstrate the value of this type of collection policy in view of the issues raised and what paths it can point to, taking the opportunity to conclude by suggesting as an answer to the questions the adaptation of participatory experiences within the scope of heritage and musealization policies associated to aural objects.
Keywords: phonography; collection; museum; popular music; streaming platforms